Combined pathology of various organs and systems in children with congenital hoan atresia - Alan I. Asmanov; Natalya D. Pivneva; Olga I. Belova (Consilium Medicum)
Background. Choana atresia is a "red flag" diagnosis that requires further examination for possible concomitant abnormalities, as children with this condition often have complex comorbidities that can significantly affect their prognosis, treatment options, and anesthetic risks.